Hubungan Motivasi Ibu Hamil, Peran Bidan Dan Pola Makan Terhadap Keefektifan Tablet Fe Di Puskesmas Ciawi: The Relationship between Pregnant Women's Motivation, the Role of Midwives, and Diet on Effectiveness Fe Tablets at Ciawi Community Health Center - Dinanti, Intan Selvia Tri (Dohara POAJ, 2024)
Introduction: Iron (Fe) tablet is the most important trace element for humans. The effectiveness of Fe tablets is something that is expected to achieve the maximum goal in the absorption of Fe tablets in the body. Motivation, the role of the midwife, and dietary habits are factors that can affect the effectiveness of Fe tablets. This study aims to determine the relationship between mothers’ motivation, the role of midwives, and dietary habits on the effectiveness of Fe tablets at Ciawi Community Health Center in 2023. Methods: Using descriptive analytics with a cross-sectional approach. The sampling technique used is simple random sampling with 57 samples. Results: The results showed that there was a relationship between the motivation of pregnant women (0,000); the role of the midwife (0,039); and eating patterns (0,007) toward compliance with Fe tablets in pregnant women. Discussion: The conclusion is that there is a significant relationship between the motivation of pregnant women, the role of midwives, and diet toward compliance with Fe tablets for pregnant women at the Ciawi Bogor Health Center in 2023. Suggestions for pregnant women to be able to increase their knowledge and understanding of the importance of consuming Fe tablets during pregnancy under the directions given by health workers to improve the welfare and health of the mother and the fetus she contains.